Digitalization and Spiritual Transformation: A Phenemenological Study of Young Catholic Priest in Diocese of Palangka Raya - Manik, Resmin; Jimmy, Andreas (Universitas Dharma Wacana, 2025)
This research explores the phenomenological experiences of young Catholic priests in the Diocese of Palangkaraya in constructing their spirituality amid digital transformation and the cultural expectations of the Dayak community. Using a mixed-methods sequential explanatory design with Interpretative Phenomenological Analysis (IPA) involving 10 priests aged 30-40 years with 1-10 years of ordination, the research revealsfourmainthemes:thedualityofdigitalexperienceinspirituality, negotiationoftensionbetweentraditionandmodernity,reconstructionof priestlyidentity,andspiritualadaptationstrategies.Quantitativeanalysis shows significant correlations between digital competence (r=0.68, p<0.01) and cultural intelligence (r=0.72, p<0.01) with digital pastoral adaptation. Qualitative findings reveal that young priests experience